L‐Leucine improves the anaemia in models of Diamond Blackfan anaemia and the 5q‐ syndrome in a TP53‐independent way. (7th August 2014) - Narla, Anupama; Payne, Elspeth M.; Abayasekara, Nirmalee; Hurst, Slater N.; Raiser, David M.; Look, A. Thomas; Berliner, Nancy; Ebert, Benjamin L.; Khanna‐Gupta, Arati
Summary Haploinsufficiency of ribosomal proteins (RPs) and upregulation of the tumour suppressor TP53 have been shown to be the common basis for the anaemia observed in Diamond Blackfan anaemia and 5q‐ myelodysplastic syndrome. We previously demonstrated that treatment with L‐Leucine resulted in a marked improvement in anaemia in disease models. To determine if the L‐Leucine effect was Tp53‐dependent, we used antisense MOs to rps19 and rps14 in zebrafish; expression of tp53 and its downstream target cdkn1a remained elevated following L‐leucine treatment. We confirmed this observation in human CD34+ cells. L‐Leucine thus alleviates anaemia in RP‐deficient cells in a TP53‐independent manner.